OPTIMALISASI PENDAMPINGAN PENULISAN ARTIKEL ILMIAH BAGI MAHASISWA PROGRAM STUDI AKUNTANSI SYARIAH - Mahmudah, Nufidatul; Windasari, Ihsanul (Jurnal Pengabdian Bukit Pengharapan, 2024)
Writing scientific articles is an essential skill that students must possess to act as agents of change in society. Students of the Sharia Accounting Study Program are expected to produce high-quality scientific works and publish them in reputable journals. However, many students face challenges in this writing process, including a lack of understanding of the structure and format of scientific articles, as well as difficulties in conducting in-depth research. To address this, community service activities in the form of scientific article writing assistance have been conducted. The methods used include lectures, discussions, and intensive mentoring. Participants gained an in-depth understanding of the structure and format of scientific writing, as well as tips for successful publication. During the mentoring sessions, students were encouraged to draft simple research articles and write them in the form of abstracts. The results of these activities showed a significant improvement in students' knowledge and skills related to scientific writing. Students who previously did not know how to write scientific articles are now able to produce works ready for publication in academic journals. In conclusion, this mentoring activity has successfully enhanced students' ability to write scientific articles and sparked their enthusiasm and active participation in the learning process. It is recommended to increase the frequency of training, develop more comprehensive learning modules, and encourage collaboration between students, lecturers, and researchers to produce high-quality scientific works.